Optimization of zirconium and yttrium content in 17Cr ferritic ODS steel through Taguchi analysis. (2021) - Sellamuthu, Prabhukumar; Dharmalingam, G.
Abstract: The present investigation on an optimum level of zirconium and yttrium content were identified using Taguchi analysis. This effect is the most influencing factor to obtain better mechanical properties and microstructure of 17Cr Ferritic ODS Steel. The 17Cr Ferritic ODS steel alloy was developed from 430L pre-alloyed powder followed by a mechanical alloying process. The 20 h of milled powder were consolidated through vacuum hot pressing (VHP) at 1200 °C and pressure level of 60 MPa with a vacuum level of 10 -3 Torr. Hot pressed samples were characterized using TEM analysis. Namely optimization of three parameters such as zirconium, yttrium, and sintering temperature was done in the present study through the design of experiments followed by the Taguchi approach. ANOVA all-encompassing of signal to noise ratio was used to optimize the process parameters through L9 orthogonal array. It has predicted the response variables of density and hardness. The zirconium and yttrium content is the most customary factor subsequently the VHP to improving the density and mechanical properties of 17Cr Ferritic ODS steel. It was confirmed through the regression equation and confirmation test.